Institutional issues on disaster risk reduction and management - Sonny N. Domingo (Philippine Institute for Development Studies (PIDS), 2017)
Ensuring the realization of the full potential of the incumbent disaster risk reduction and management (DRRM) policy requires appropriate sectoral and institutional translation of its espoused principles; reflecting more refined institutional arrangements and policy and resource support. Strengthening institutional structures and crafting the appropriate platform for DRRM require important decisions, particularly on the issue of mandate, jurisdiction, and response capability. A functionally superior platform would help address issues on institutional capacity and leadership, expediency of disaster response, stakeholder participation, and community preparedness and protection. DRRM tenets have to be internalized, imbedded, and exactingly practiced within institutions inside and outside of the bureaucracy. This study aims to contribute to the current policy debate on the appropriate legislative vehicle toward institutional augmentation and reform.
Keywords: 330; Disaster Risk Reduction and Management; DRRM Institutional Platform; Institutional Analysis